Vitamin D Insufficiency Predicts Susceptibility of Parathyroid Hormone Reduction after Total Thyroidectomy in Thyroid Cancer Patients - Yan Zhang; Weihui Zheng; Yuanyuan Huang; Chao Chen (International Journal of Endocrinology)
Objective. Given its role in the regulation of calcium and PTH levels, vitamin D was presumed as a potential predictor of postoperative hypoparathyroidism. However, the reports about their association were controversial. This study aims to reveal the relationship between preoperative vitamin D and postoperative parathyroid hormone (PTH). Methods. A total of 242 papillary thyroid cancer (PTC) patients who underwent total thyroidectomy (TT) during the period from June 2016 to December 2017 at our hospital were enrolled. Patients were divided into two groups, HypoP and Non-HypoP groups, based on postoperative PTH < 15.0 or ≥15.0 pg/mL, and ΔPTH50+ and ΔPTH50− groups, based on postoperative PTH reduction ratio ≥ 50% or <50%. Clinicopathological features and laboratory data were compared between two sets of groups. Results. Preoperative PTH level was lower in the HypoP group than in the Non-HypoP group (42.83 vs. 47.52 pg/mL, p=0.018). No significant difference of vitamin D insufficiency was found between the HypoP and Non-HypoP groups (80.8% vs. 74.1%, p=0.226). The rate of vitamin D insufficiency was higher in the ΔPTH50+ group than in the ΔPTH50− group (82.6% vs. 68.4%, p=0.010). By multivariate logistic regression analysis, vitamin D insufficiency was an independent predictor of postoperative PTH reduction ratio ≥ 50% (OR = 2.2, p=0.017). Conclusion. Vitamin D insufficiency is not associated with postoperative PTH in PTC patients undergoing TT. However, vitamin D insufficiency is an independent predictor of postoperative PTH reduction ratio.